Neurofinance. (January 2019) - Miendlarzewska, Ewa A.; Kometer, Michael; Preuschoff, Kerstin
Neurofinance is a relatively new area of research that strives to understand financial decision making by combining insights from psychology and neuroscience with theories of finance. Using behavioral experiments, neurofinance studies how we evaluate information about financial options that are uncertain, time-constrained, risky, and strategic in nature and how financial decisions are influenced by emotions, psychological biases, stress, and individual differences (such as gender, genes, neuroanatomy, and personality). In addition, it studies how the brain processes financial information and how individual decisions arise within it. Finally, by combining these experiments with computational models, neurofinance aims to provide an alternative explanation for the apparent failure of classic finance theories. Here we provide an introduction to neurofinance and look at how it is rooted in different fields of study. We review early findings and implications and conclude with open questions in neurofinance.